KEUNGGULAN KOMPETITIF YANG DALAM MENCIPTAKAN INOVASI UNTUK KEWIRAUSAHAAN STRATEGIS - Bilgies, Ana Fitriyatul (An-Nisbah: Jurnal Ekonomi Syariah, 2017)
At the moment in the environment of  competitive advantage use for companyneeds to be very agile and adaptive. While often unable to make a certainlevel of performance based on technology on existing progress, the company isalso came often to login of  in the new technology emerging. How to addressentrepreneurship strategically as a way which the company simultaneouslyexploit competitive advantage they are now while explore for opportunitiesfor the future . On this Reaching based on balance between exploration andexploitation of  consists of more than just allocated of  resources in comparable between the two the process. And so as be discussed, For the exploration to the exploitation of  is process that it should be, structure and culturally distinct.